Ukrainian state of hetman Pavlo Skoropadsky: ideals and realities of the state - Rumiantsev, Vyacheslav (Problems of legality, 2022)
The article reflects the main processes of building during the development of the Ukrainian state of Hetman P. Skoropadsky. P. Skoropadsky’s views on the Ukrainian nation, the Ukrainian state and its form, the relationship of the then political and national forces, the place of Ukraine in the geopolitical space of that time, the main directions and content of the state process, its achievements and miscalculations are analyzed. The views of P. Skoropadsky on the content of the state process in Ukraine in 1918 are analyzed. First of all, on the form of the Ukrainian state - independent or federal. We are talking about the form of government of the Ukrainian state and its political regime. Internal and external factors that influenced this are analyzed. The content of the main directions of activity of the hetman government is investigated both inside the state (central and local government, judicial system, armed forces, agrarian policy, social and cultural construction) and outside (international recognition, establishment of diplomatic relations). It is concluded that the emergence of the Ukrainian state of Hetman P. Skoropadsky was a continuation of the process of creation during the Ukrainian revolution of 1917-1921. This process took place in difficult conditions of the First World War and this circumstance determined the peculiar form of the Ukrainian state and its activities, sometimes they were contradictory and had disagreements with the ideals of the state, which ultimately led to the decline of the Ukrainian state.